Obstructed ileocaecal tuberculosis with splenic tuberculosis and solid pseudopapillary tumour of tail of pancreas in an immunocompetent woman - Paramasivam, Surendran (BMJ Case Rep, 2020)
A 22-year-old young woman presented with fever, lower abdominal pain and vomiting for 20 days. She had persistent fever and abdominal pain. Fever panel was negative. Clinical features were suggestive of subacute small bowel obstruction. Contrast-enhanced CT abdomen showed thickening of distal ileum, ileocaecal junction and caecum with conglomerate necrotic nodal mass in the ileocolic mesentry along with a lesion in the tail of pancreas. Patient was discussed with multidisciplinary team and decided to undergo a single-stage procedure after adequate nutritional optimisation. During optimisation, she underwent acute obstruction and hence taken up for emergency laparotomy proceeded to right haemicolectomy with distal pancreatectomy and splenectomy 4 weeks after the time of admission. Histopathology showed ileocaecal tuberculosis and solid pseudopapillary tumour with margins free of tumour. Approach of obstructed ileocaecal tuberculosis in the setting of incidental diagnosis of solid pseudopapillary tumour of pancreas in a moribund patient was challenging.